Tribalism and democracy in the arab world: a sociological study of the Arab mind and its perception of democracy through the events of the Arab spring - Merah , Souad; Tahraoui, Ramdane (2015)

(untitled)
Arab Spring Movements, Arab Uprising, awakening, and Arab Revolutions, are among many other terms which denoted the wave of revolutionary events, protests, and demonstrations that erupted on December 2010 in Tunisia, then in Libya, Yemen, Egypt, Bahrain, and spread up to Syria, Morocco, Jordan, Algeria, Sudan, Iraq, and Kuwait. Minor demonstrations also took place in Saudi Arabia, Oman, and Lebanon. Some of these protests turned violent and were militarized later such as in the case of Libya and Syria. In terms of outcomes, the results of this ongoing uprising are quietly mixed, while four different Arab governments have been overthrown (Tunisia, Egypt, Libya and Yemen), not much has so far been achieved in the other Arab countries. The early peaceful demonstrations in Syria turned violent after government crackdowns and the conflict between the autocratic Baath Government of Syria and its opponent turned into an ugly and bloody large scale civil war. There has been much controversy about the true nature and objectives of those movements and who stands behind them. Though the majority of the public voices and opinions are still throwing its support to Arab Spring, many are also skeptical about the real instigators, intrinsic motives and the long term agenda. The common denominator that brings together most of the Arab spring revolutions is the fact that as soon as they succeed in toppling the dictatorial regimes targeted by these revolutions, they themselves drop into a state of weakness and anarchy, and quickly, divisions and wide cracks within the social structure become very visible. Ethnic, tribal or sectarian divisions lead, in most cases, to an inevitable armed confrontation. The other noticeable common divisor in post Arab Spring is the horrible dissolution of State institutions, insecurity, and economic stagnation. Such manifestations indicate one of two things: either the opposition forces that overthrew dictatorial regimes in the Arab world have a project of opposition only, and they lacked an alternative and better project of governance, or that the Arab mentality in particular, whether ruling or ruled, in opposition or in power, is not ready yet to shoulder the responsibilities and consequences of democracy. In this paper we will try to analyze the Arab mentality and its disposition towards change and evolution. Also, we will try to answer the following big question: Is the Arab society with all of its political, social, economic and cultural institutions, ready to experience democracy after decades of totalitarian, dictatorial and religious sectarian rule? Could democratic values and governance be practiced in a society without being fostered in the mindset of people? To what extent are the democracy worshippers themselves democrats in their quest? All these questions deserve a sincere and candid answer in this inquiry. To understand the Arab mind set we have first to analyze the long and complicated cultural heritage which was formed throughout the history of Arabia and how it still plays a great role in the way Arabs perceive themselves and the world around them.